2005
DOI: 10.1074/jbc.m414137200
|View full text |Cite
|
Sign up to set email alerts
|

Ohanin, a Novel Protein from King Cobra Venom, Induces Hypolocomotion and Hyperalgesia in Mice

Abstract: We have identified, purified, and determined the complete amino acid sequence of a novel protein, ohanin from Ophiophagus hannah (king cobra) venom. It is a small protein containing 107 amino acid residues with a molecular mass of 11951.47 ؎ 0.67 Da as assessed by electrospray ionization-mass spectrometry. It does not show similarity to any known families of snake venom proteins and hence is the first member of a new family of snake venom proteins. It shows similarity to PRY and SPRY domain proteins. It is non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 26 publications
1
72
0
Order By: Relevance
“…Conversely, the unpublished ohanin precursor available on databases (AAR07992.2) has its starting codon only 20 positions upstream from the mature N terminus ( Figure 5A). The precursor indicates also a C-terminal processing, since the molecules purified from the venom end 63 residues before the stop codon (Pung et al 2005). This processed C terminus is different from other B30.2 proteins ( Figure 5B); it is shorter and predominantly hydrophobic (see plot in Figure 5A), perhaps suggesting a membrane association during the maturation process.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Conversely, the unpublished ohanin precursor available on databases (AAR07992.2) has its starting codon only 20 positions upstream from the mature N terminus ( Figure 5A). The precursor indicates also a C-terminal processing, since the molecules purified from the venom end 63 residues before the stop codon (Pung et al 2005). This processed C terminus is different from other B30.2 proteins ( Figure 5B); it is shorter and predominantly hydrophobic (see plot in Figure 5A), perhaps suggesting a membrane association during the maturation process.…”
Section: Resultsmentioning
confidence: 92%
“…For the ohanin-like, since the similarity is high and this class of protein was only recently described (Pung et al 2005), being reported also in lizards (Fry et al 2006), we believe that a common origin is very probable. For the diverging 3FTx, the phylogenetic tree also suggests a common and ancestral origin with Colubridae and Elapidae toxins, but in this case, the evidence is not very strong, since the uPAR (domain 2) also was in the group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The liquid chromatography/MS profile of O. hannah venom (44) showed the presence of a 7,535.67 Ϯ 0.60 Da protein, similar to the expected molecular mass of the protein being characterized. This protein was purified from the crude venom using a two-step chromatographic approach.…”
Section: Resultsmentioning
confidence: 94%
“…In reptile venoms, they are an ancestral type shared between lizard and snake venoms (56). The bioactivity of the lizard form remains to be elucidated, but the isoform characterized from Ophiophagus hannah snake venom produces hypolocomotion and hyperalgesia, perhaps by acting directly on the central nervous system (125). SPRY toxins in stonefish venoms produce lethal hemolysis through pore formation in cell membranes while inducing potent endothelium-dependent hypotension and also irreversibly interfering with neuromuscular function (29,88,146).…”
Section: Spry/concavalin A-like Lectinsmentioning
confidence: 99%